The flavor of faba bean ingredients and extrudates: Chemical and sensory properties. (December 2022) - Tuccillo, Fabio; Kantanen, Katja; Wang, Yaqin; Martin Ramos Diaz, Jose; Pulkkinen, Marjo; Edelmann, Minnamari; Knaapila, Antti; Jouppila, Kirsi; Piironen, Vieno; Lampi, Anna-Maija; Sandell, Mari; Katina, Kati
Graphical abstract: Highlights: FPC Faba bean protein concentrate was bitter, had a strong taste and aftertaste, and caused a drying mouthfeel. Bitterness and drying mouthfeel were linked to free phenolics, vicine, and convicine. Faba bean flour had a mild taste, whereas FPI faba bean protein isolate had cereal and off-odors and flavors. Cereal and pea odors and flavors were linked to several lipid oxidation products. High-moisture extrusion inactivated lipase and lipoxygenase. Abstract: Faba bean, processed into ingredients (flour, protein concentrate, protein isolate), can be extruded to meat alternatives with a fibrous texture. Despite its importance for consumer acceptance, not enough is known about the flavor of faba bean ingredients nor about the chemical and sensory changes caused by high-moisture extrusion. Therefore, the aim of this work was to describe the flavor of faba bean ingredients and the corresponding extrudates and to understand how their composition affects the perception of sensory attributes. Firstly, faba bean protein ingredients and extrudates were characterized for lipid-degrading enzymatic activities, flavor precursors, and volatile and non-volatile flavor-active compounds. Secondly, sensory profiling was conducted. Thirdly, partial least squares regression was applied to understand the relationship between chemical and sensory data. This study showed that faba bean protein concentrate had the strongest taste and aftertaste (respectively 7 and 6, on a 0–10 intensity scale), bitterness (6–7), and pea flavor and odor (respectively 6 and 5), whereas faba bean protein isolate had the strongest cereal flavor (4) and odor (4), and off-flavor (2) and off-odor (3). Faba bean flour had the mildest flavor. High-moisture extrusion brought several chemical changes to the ingredients, including the formation of several volatile compounds and inactivation of lipid-degrading enzymes. Only traces of tannins were found in extrudates. The presence of free phenolics, vicine, and convicine was linked to strong taste and aftertaste, bitterness, and a drying sensation of the mouth, whereas lipid oxidation products were related to pea, cereal, and off-odors and flavors.